2006
DOI: 10.1177/014556130608501216
|View full text |Cite
|
Sign up to set email alerts
|

Secretions, Occlusion Status, and Swallowing in Patients with a Tracheotomy Tube: A Descriptive Study

Abstract: Weconducted a prospe ctive, descriptive study of40 tracheotom ized patients to investigate the relationships between (1) levels of accumulated oropharyngeal secretions and laryngeal penetration/aspiration status, (2) secretion levels and tube-o cclusion status, and (3) tube-occlusion status and aspiration status .Assessments ofsecretion status were quantifi ed with the use ofa 5-point rating scale. All evaluations were made by fib eroptic endoscop ic evaluation of swallowing. Wefound that pati ents with higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 18 publications
2
35
0
2
Order By: Relevance
“…Specifically, no significant differences were found for either laryngeal excursion or hyoid bone displacement during swallowing based on the presence or absence of either the Passy Muir or Blom valve. This corroborates previous research which showed that presence/absence of a tracheotomy tube [3,4,8,9] and occlusion status of a tracheotomy tube [5][6][7]10] had no significant effect on hyolaryngeal movement. Aspiration status was also not effected by use of either the Passy-Muir or Blom one-way speaking valves.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Specifically, no significant differences were found for either laryngeal excursion or hyoid bone displacement during swallowing based on the presence or absence of either the Passy Muir or Blom valve. This corroborates previous research which showed that presence/absence of a tracheotomy tube [3,4,8,9] and occlusion status of a tracheotomy tube [5][6][7]10] had no significant effect on hyolaryngeal movement. Aspiration status was also not effected by use of either the Passy-Muir or Blom one-way speaking valves.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with previous research which found that re-establishing the closed aerodigestive system during expiration was not beneficial in reducing incidence of aspiration [16] and had no effect on swallow duration measures or extent of hyolaryngeal movement [12]. These results also expand upon and corroborate reports that found no causal relationship between aspiration status and presence of a tracheotomy tube [1,2] and no change in incidence of aspiration dependent upon occlusion status of a tracheotomy tube [5][6][7]10]. Therefore, it is not the tracheotomy tube per se, but rather the underlying critical medical co-morbidities that necessitated a tracheotomy and placement of a tracheotomy tube in the first place that cause dysphagia [1,2].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The incidence of aspiration in adults with tracheostomy is reported to be 30% to 50%, and the risk of aspiration is directly related to the amount of oropharyngeal secretion [7,8]. Also, pneumonia rates were higher even in tube feeding patients, whom food aspiration is less likely to occur, indicating a possibility of pneumonia from salivary aspiration [8]. These findings underscore the need to evaluate salivary aspiration in patients with tracheostomy, followed with appropriate management to prevent pneumonia in high risk patients.…”
Section: Introductionmentioning
confidence: 99%